THE CONSTRUCTION OF PHYSICAL REHABILITATION PROGRAMS IN THE PREOPERATIVE PERIOD FOR PATIENTS THAT WILL REMOVE OF INTERVERTEBRAL DISC’ PROLAPSE IN THE LUMBAR SPINE - Lazarieva, E.B.; Kormiltsev, V.V.; Prusik, Krzysztof; Cieślicka, Mirosława (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
The ineffectiveness of conservative treatment will make the need for surgery in 4-5% of patients suffering from low back pain with hernias of the lumbar and sacral spine. Despite the surgical removal of the source of compressed roots, nerves and blood vessels, require a comprehensive system of rehabilitation therapy in order to eliminate manifestations of disease and relief of disease progression. The aim of the work is to substantiate the general approaches for the using of physical rehabilitation and diagnostics static component of the dynamic stereotype in the preoperative period in patients to remove intervertebral disc prolapse. The materials and methods. There was examined 96 with low back pain. Methods are applied in this research: analysis of a literature, observation methods. Results. In conjunction with the physician was determined "diagnosis for rehabilitation" and "prognosis of the rehabilitation". The formulation of the basis of the diagnosis for rehabilitation was performed through the examination during the rehabilitation (as a taking an anamnestic data, examination and palpation), studies of intact sensory and motor functions, the results of objective research tool. Conclusions. The identification of preserved anatomical and functional entities, the definition of the initial level of compensation for lost functions and forecast further recovery is a fundamental approach to program development in the preoperative period in patients with low back pain aimed at the removal of intervertebral disc herniations.